Mrs. Honey's hat - Adams, Pam. (Swindon [England] ; Auburn, ME : Child's Play (International), 2007)
Every day a different creature removes an item from Mrs. Honey's large and outlandish hat, leaving behind something new in its place, so that by the end of the week she has an entirely new hat.
2.6
K-3.
K-3
Keywords: Hats -- Juvenile fiction; Hats -- Fiction; Hats -- Fiction; Picture books for children